Employee Capital Plans performance through the lens of the participant – how to (better) measure and inform about the returns - Barembruch, Adam; Bielawska, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In recent decades, an increased effort to increase private retirement savings can be observed, especially in countries where public pensions have been the main source of livelihood during retirement. To increase participation in occupational as well as individual pension plans, states often use financial incentives (personal income tax reductions, preferential tax rates, subsidies). However, experience from studies in various countries shows that these incentives may not be efficient and/or attract mainly high earners. Mobilizing Poles to save for retirement in light of the paradigm shift in pension security in Poland caused by the 1999 reform has proven to be a major challenge. Given the mediocre development of the private pension plan market, a new type of workplace pension plans based on automatic enrollment called Employee Capital Plans (ECP) began to be implemented in 2019. However, despite the plan’s favorable funding mechanism, especially from the perspective of low- and middle-income earners, participation remains low. In the article, we argue that a change in the manner in which program participants are being reported their earned rates of return could increase interest in ECP participation. Following the investment performance of 60 FZDs, operating within the framework of ECP in Poland, we show that the total returns presented by the managers of FZDs and Polish FSA are lower than the returns measured from the perspective of participant contributions using the IRR method. Significantly higher results are also achieved by those with low earnings, who can make reduced contributions to ECP. Thus, we recommend the introduction of a standard for the presentation of ECP investment results from the participant’s point of view, taking into account the ECP financing mechanism.
Keywords: IRR; investor perspective; employee capital plans; defined-date funds; state subsidies